Evolution of the Kondo lattice and non-Fermi liquid excitations in a heavy-fermion metal - S. Seiro (Nature Portfolio, 2018)
The competition between Kondo correlations and magnetic ordering in heavy fermion materials leads to emergent physics that is not fully understood. Seiro et al. show inter-site Kondo correlations only dominate over local ones at temperatures well below the single-ion Kondo temperature but this is a prerequisite for quantum critical behavior.